1980
DOI: 10.1007/bf03179164
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory evaluation of poison-base for the control ofFunambulus pennanti

Abstract: Funambulus pennanti, the northern palm squirrel preferred wheat in its different forms out of ten cereals and oil seeds offered. It is revealed that the squirrels are selective feeders since out of eleven forms, i.e., whole, cracked, roasted and flour, wheat was found to be most palatable in seven trials followed by bajra (three trials) and jowar once. The addition of vegetable oils, salt and sugar does not enhance the bait acceptance. However, they preferred sugar in comparison to salt, and arachis and sesame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
2002
2002

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
(1 reference statement)
0
1
0
Order By: Relevance
“…(ground squirrels) and Thomomys bottae (pocket gophers) seem little influenced by added sugar. Soni et al (1980) found that neither sugar nor vegetable oils enhanced bait consumption in Funambulus pennanti (northern palm squirrel) in India. However, both sugar and vegetable oil were found to enhance bait consumption in Rattus meltada (soft-furred field rat) in India (Chopra et al, 1984) and Arvicanthis niloticus (Nile rat) in Egypt (Suliman et al, 1984).…”
Section: Sugar and Other Sweetening Agentsmentioning
confidence: 99%
“…(ground squirrels) and Thomomys bottae (pocket gophers) seem little influenced by added sugar. Soni et al (1980) found that neither sugar nor vegetable oils enhanced bait consumption in Funambulus pennanti (northern palm squirrel) in India. However, both sugar and vegetable oil were found to enhance bait consumption in Rattus meltada (soft-furred field rat) in India (Chopra et al, 1984) and Arvicanthis niloticus (Nile rat) in Egypt (Suliman et al, 1984).…”
Section: Sugar and Other Sweetening Agentsmentioning
confidence: 99%